The Process of Tectonic Inversion and Disintegration in the Dasanjiang Unified Basin, Northeast China: Constraint From Low-Temperature Thermochronology - Zhang, Yunpeng; Tang, Yan; Wang, Shan; Guo, Wang; Han, Wei; Ma, Shangwei; He, Zhengyang; Ren, Jianye (Frontiers in Earth Science, 2022)
The Dasanjiang basin group in Northeast China contains more than ten Mesozoic–Cenozoic sedimentary basins. Much evidence shows that they were a unified large-scale depression lacustrine basin in the Early Cretaceous; however, destruction processes and mechanisms after the formation of the unified lacustrine basin are some of the key issues restricting basic research and oil and gas exploration in the Dasanjiang area. In this study, we carried out low-temperature thermochronology and thermal history inversion on samples from the main basins in the Dasanjiang area to finely restore the destruction process of the unified basin. The results show that since the Early Cretaceous, the Dasanjiang area has experienced three major positive tectonic inversions: 100 Ma~90 Ma, 73 Ma~40 Ma, and 23 Ma~5 Ma. The unified basin was destroyed by compression and uplift and gradually disintegrated. The basin gradually changed from initial unified evolution to differential evolution and finally formed the isolated appearance of each basin. The aforementioned three-stage positive tectonic inversion time limits basically corresponded to the changing periods in the movement direction, subduction angle, and movement speed of the paleo–Pacific Ocean plate. It is believed that the movement and reorganization events of the plates on the Pacific side dominated the formation, destruction, and disintegration of the Dasanjiang prototype basin, which was the main dynamic mechanism of the tectonic evolution of the Mesozoic and Cenozoic basins in the study area and Northeast China.